SISTEM ANALISIS KINERJA DENGAN REGRESI BANK SYARIAH INDONESIA - Mahrus Ali; Hadi Sucipto (Prosiding Seminar Nasional Sains, Teknologi, Ekonomi, Pendidikan dan Keagamaan (SAINSTEKNOPAK), 2023)
Abstract This study aims to examine several factors that influence the performance of Indonesian Islamic banks by using the variables Return On Assets (ROA), Operating Expenses Operating Income (BOPO), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposit Ratio ( FDR) and Potential Losses (PK). The data used in the study took secondary data from the website of the Financial Services Authority (OJK) from the recapitulation of reports on Islamic banks throughout Indonesia, the data was taken from 2011 to 2020 which is a combination of time series and cross section data. The analysis technique used is multiple linear regression. The results of the study after being calculated using SPSS, the value of t table is 2.776 and the value of F table is 5.05, the end result of the hypothesis (H6) is accepted, which means that the variables X1, X2, X3, X4, X5 have a simultaneous effect on Y. Then the ROA value simultaneously influenced by the value of BOPO, CAR, NPF, FDR and PK. Keywords: shariah bank, performance, regression Abstrak Studi ini bertujuan untuk menguji beberapa faktor yang mempengaruhi kinerja bank syariah Indonesia dengan menggunakan variabel Return On Asset (ROA), Beban Operasional Pendapatan Operasional (BOPO), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR) dan Potensi Kerugian (PK). Data yang digunakan dalam studi mengambil data sekunder dari website Otoritas jasa keuangan (OJK) dari rekapitulasi laporan bank syariah se Indonesia, data yang diambil mulai tahun 2011 sampai dengan tahun 2020 yang merupakan data gabungan Time series dan cross section. Teknik analisis yang digunakan adalah regresi linier berganda. Hasil penelitian setelah dihitung menggunakan SPSS maka nilai t table 2,776 dan nilai F table 5, 05 yang hasil akhirnya hasil hipotesis (H6) diterima yang artinya variabel X1, X2, X3, X4, X5 berpengaruh secara simultan terhadap Y. Maka nilai ROA secara simultan dipengaruhi oleh nilai BOPO, CAR, NPF, FDR dan PK. Kata kunci: bank syariah, kinerja, regresi